2020
DOI: 10.24843/jpsa.2020.v02.i01.p05
|View full text |Cite
|
Sign up to set email alerts
|

ANTIFUNGAL ACTIVITIES OF ETHANOL EXTRACT OF ROSEMARY LEAF (Rosemarinus officinalis L.) AGAINST Candida albicans

Abstract: Background: This study was a preliminary study aimed to investigating the in vitro activity of rosmarinic acid contained on Rosemary leaves (Rosemarinus officinalis L.) on the Candida albicans. Rosmarinic acid can be an inhibitor of the RTPase enzyme in the fungus Candida albicans. Objective: This study is expected to provide information in the development of science about the antifungal activity of ethanol extract of Rosemary leave (Rosmarinus officinalis L.) againsts C.albicans. The recent research was an la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
1
3
0
6
Order By: Relevance
“…The rosemary extracts were potent against Gram-positive and Gram-negative bacteria in a study by Mahmood et al [ 56 ]. In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans . Rosemary extract had antiviral efficacy against HSV-1 and HSV-2, according to Al Mergin et al [ 3 ].…”
Section: Resultssupporting
confidence: 92%
“…The rosemary extracts were potent against Gram-positive and Gram-negative bacteria in a study by Mahmood et al [ 56 ]. In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans . Rosemary extract had antiviral efficacy against HSV-1 and HSV-2, according to Al Mergin et al [ 3 ].…”
Section: Resultssupporting
confidence: 92%
“…Os extratos etanólicos de alecrim citronela, limão e nim apresentaram atividade antifúngica em concentrações mais baixas, no entanto o extrato de arruda foi capaz de controlar as linhagens de C. albicans clínicas na concentração 25% e 50% (Tabela1). Estudos realizados por Swari et al (2020), Proškovcová et al, (2021), Shafa et al (2021) evidenciaram a eficácia dos extratos e óleos essenciais destas plantas no controle de C. albicans.…”
Section: Resultsunclassified
“…Além disso, o potencial dessas espécies para apresentar resistência e resistência cruzada a drogas azólicas, pode levar ao fracasso das estratégias terapêuticas (Delaloye & Calandra, 2014). Nos últimos anos, o uso de óleos essenciais e de extratos de plantas como uma abordagem para melhorar a eficácia de agentes antifúngicos e reduzir os níveis de resistência antifúngica tem sido proposto (Kumar, 2020;Swari et al, 2020;Donadu et al, 2021, Manso et al, 2021 Tabela 1: Concentração inibitória mínima (CIM) e concentração fungicida mínima (CFM) de extratos etanólicos de plantas no controle in vitro de Candida albicans. Resultados divergentes sobre eficácia podem estar influenciados pelo tempo de maceração da folha de alecrim para obtenção do extrato etanólico das folhas de alecrim, o qual poderia interferir na concentração dos componentes quimicos do produto final da extração (Swari et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…2). With the increasing of rosemary extract concentration levels from 20 to 60%, the inhibition effect showed a significant reduction against C. albicans (Swari et al 2020), while with the increasing of rosemary extract concentration levels from 20 to 60%, the inhibition effect showed an increasing trend against S. aureus (Fig. 2).…”
Section: Antibacterial Activity Inhibition Zone Diameter (Izd) Determmentioning
confidence: 91%